Infectıon of Hepatıtıs B Vırus and Hepatıtıs C Vırus in Thalassemıa - Setiawan, Doni; Istianah, Euis Tia; Ariani, Dini; Setiawan, Henri (Medical Laboratory Technology Journal, 2025)
Thalassemia disease remains incurable and causes many complications. People with thalassemia major require routine lifelong blood transfusions. A main risk of transfusion is infection with diseases transmitted through blood, which is among the most frequent causes of death in thalassemia patients. Transfusion-transmitted infections (TTIs) include hepatitis B and hepatitis C. This study aimed to determine the prevalence of hepatitis B and C in thalassemia patients in Ciamis Regency and examine the relationship between transfusion frequency and these infections. The method was a cross-sectional study on thalassemia patients who received blood transfusions. The study included 191 thalassemia patients at Ciamis Hospital from January to June 2023. Purposive sampling selected 89 patients as the sample. Hepatitis B and C tests used immunochromatography. The prevalence of Hepatitis C Virus and Hepatitis B Virus infections in thalassemia patients in Ciamis Regency was 2.2% and 3.4%, respectively. The chi-square test showed a significant relationship (p < 0.05) between transfusion frequency and hepatitis B and C infection in thalassemia patients. This result suggests a risk of hepatitis B and C infection. Thalassemia patients are potentially susceptible to blood-borne Hepatitis C Virus and Hepatitis B Virus. These infections increase morbidity due to transfusion therapy. Routine inspection for Hepatitis B Virus and Hepatitis C Virus is essential for thalassemia patients. These results emphasize the need for strict screening protocols in blood transfusion processing.